Prognosis of Upfront Surgery for Pancreatic Cancer: A Systematic Review and Meta-Analysis of Prospective Studies - Pecorelli, Nicolò; Licinio, Alice W.; Guarneri, Giovanni; Aleotti, Francesca; Crippa, Stefano; Reni, Michele; Falconi, Massimo; Balzano, Gianpaolo (Frontiers in Oncology, 2022)
Background: The rate of patients with pancreatic ductal adenocarcinoma (PDAC) receiving neoadjuvant chemotherapy is increasing, but upfront resection is still offered to most patients with resectable or borderline resectable disease. Encouraging data reported in adjuvant chemotherapy trials prompts surgeons towards upfront surgery, but such trials are subject to a significant selection bias. This systematic review aims to summarize available high-quality evidence regarding survival of patients treated with upfront surgery for PDAC. Methods: Pubmed, Cochrane, and Web of Science Databases were interrogated for prospective studies published between 2000 and 2021 that included at least a cohort of patients treated with upfront surgery for resectable or borderline resectable PDAC. The Cochrane Collaboration’s risk-of-bias tool for randomized trials (RoB-2) was used to assess risk of bias in all randomized studies. Patient weighted median overall survival (OS) and disease-free survival (DFS) were calculated. Results: Overall, 8,341 abstracts were screened, 17 reports were reviewed in full text, and finally 5 articles and 1 conference abstract underwent data extraction. Included studies were published between 2014 and 2021. All studies were RCTs comparing different neoadjuvant treatment strategies to upfront surgery. Three studies included only resectable PDAC patients, two studies recruited patients with resectable and borderline resectable disease, and one study selected only borderline resectable patients. A total of 439 patients were included in the upfront resection cohorts of the 6 studies, ranging between 20 to 180 patients per study. The weighted median OS after upfront surgery was 18.8 (95% CI 12.4 – 20.6) months. Median DFS was 9 (95% CI 1.6 – 12.5) months. Resection rate was 74.5% (range 65-90%). Adjuvant treatment was initiated in 68% (range 43-77%) of resected patients. Conclusions: High-quality data for PDAC patients undergoing upfront surgery is scarce. Meta-analysis from the included studies showed a significantly shorter OS and DFS compared to recently published studies focusing on adjuvant combination chemotherapy, suggesting that the latter may overestimate survival due to the exclusion of most patients scheduled for upfront surgery.